Adaptasi Alat Ukur Learning Agility pada Mahasiswa Baru: Versi Bahasa Indonesia - Widayati, Yasa; Wahyuni, Zulfa Indira; Tresniasari, Nia; Suaidy, Sitti Evangeline I; Santicha, Ayunni; Lestari, Niken Ayu; Al-Bisyri, Yasmin Syahidah (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2025)
Students are required to be flexible and responsive learners in the midst of uncertainty and changes in global situations. Learning agility in college students allows new students to adapt and create new values when they are in ambiguous situations. Therefore, a valid learning agility instrument is needed so that the adaptation of the measuring instrument to the instrument proposed by Gravett and Caldwell (2016) is carried out to test the learning agility measuring instrument for new students by implying four dimensions, namely people agility, change agility, results agility, and mental agility. The participants of this study were 222 new students of the Faculty of Psychology, Syarif Hidayatullah Islamic State University Jakarta. Confirmatory Factor Analysis (CFA) was used as a data processing method with the help of Lisrel 8.80 software. Based on CFA analysis, it can be concluded that there are two items dropped because they are not significant in measuring the dimensions of learning agility. Keywords : learning agility, CFA, adaptation, learning